Applications and innovations in typeface design for North American Indigenous languages. Issue 1 (1st May 2020) - Schillo, Julia; Turin, Mark
In this contribution, we draw attention to prevailing issues that many speakers of Indigenous North American languages face when typing their languages, and identify examples of typefaces that have been developed and harnessed by historically marginalized language communities. We offer an overview of the field of typeface design as it serves endangered and Indigenous languages in North America, and we identify a clear role for typeface designers in creating typefaces tailored to the needs of Indigenous languages and the communities who use them. While cross-platform consistency and reliability are basic requirements that readers and writers of dominant world languages rightly take for granted, they are still only sporadically implemented for Indigenous languages whose speakers and writing systems have been subjected to sustained oppression and marginalization. We see considerable innovation and promise in this field, and are encouraged by collaborations between type designers and members of Indigenous communities. Our goal is to identify enduring challenges and draw attention to positive innovations, applications and grounds for hope in the development of typefaces by and with speakers and writers of Indigenous languages in North America.